2021
DOI: 10.2147/ott.s295063
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of the Complement Protein C1Q and Its Correlation with Immune Infiltrates in Osteosarcoma

Abstract: Background Osteosarcoma (OS) is the most widespread bone tumour among childhood cancers, and distant metastasis is the dominant factor in poor prognosis for patients with OS. Therefore, it is necessary to identify new prognostic biomarkers for identifying patients with aggressive disease. Methods Two OS datasets (GSE21257 and GSE33383) were downloaded from the Gene Expression Omnibus (GEO) and subsequently subjected to weighted gene co-expression network analysis (WGCNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…However, a common pattern of sub-type expression among the genes was observed in KIRC, LUAD, LUSC, and STAD. This pattern of gene expression is in alignment with the literature demonstrating the context-dependent expression and functions of complement components in different types of cancer [26,[46][47][48][49][50][51].…”
Section: Discussionsupporting
confidence: 88%
“…However, a common pattern of sub-type expression among the genes was observed in KIRC, LUAD, LUSC, and STAD. This pattern of gene expression is in alignment with the literature demonstrating the context-dependent expression and functions of complement components in different types of cancer [26,[46][47][48][49][50][51].…”
Section: Discussionsupporting
confidence: 88%
“…In osteosarcoma, the expression of C1Q, mostly by macrophages, negatively correlates with patient survival 8 . In pancreatic ductal adenocarcinoma (PDAC), C1q expression in primary tumors and hepatic metastasis is higher compared to normal tissue, and the presence of C1Q+M2-like macrophages is associated with worse prognosis 9 .…”
Section: C1q+ Tam In the Light Of Scrnaseqmentioning
confidence: 99%
“…Huang et al. ( 141 ) found that C1qA, C1qB, and C1qC levels were positively correlated with the number of follicular helper T cells, CD8 + T cells, and memory B cells. Moreover, the expression of these three key genes was significantly lower in metastatic osteosarcoma cell lines than in non-metastatic osteosarcoma cell lines.…”
Section: Complement Systemmentioning
confidence: 99%